Diamonds are a girl's best friend : a novel - Colgan, Jenny (William Morrow, an imprint of HarperCollinsPublishers, 2020)
Sophie Chesterton is a girl about town - she knows all the right people, goes to all the right parties, and wears all the right clothes. But deep down she suspects that her best friends are actually rather nasty, and that her lifestyle doesn't really amount to much. Her father wants her to make her own way in the world, to make him proud. But after one shocking evening her life is changed for ever. Scraping a living as an assistant to a 'glamour' photographer; living in a hovel on the Old Kent Road with four smelly boys; eating baked beans from the can - this is one spectacular fall from grace. Sophie is desperate to get her life back - but does a girl really need diamonds to be happy?